PENINGKATAN PERFORMA KEMASAN DAN STRATEGI PEMASARAN(IbM UKM Pengerajin Kerupuk Getas) - Ilham Ary Wahyudie; Zanu Saputra; Zaldy Kurniawan (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2016)
Kerupuk getas and kemplang are snacks from Bangka Island made from a mixture of mackerel and corn starch. The snacks are produced by snack food home industry. The production center located in Belinyu and Pangkalpinang City. The main problem of industry is lack of knowledge about the packaging technology and sales strategy. The product packaging is an important part of a sales strategy. In this report, the authors proved statistically that the product packaging can increase revenue. The packaging system by using vacuum packaging machine. Furthermore, sales strategy be developed into an online system.The results show that sales of products with packaging boxes significantly affect gross income partners. Correlation test showed that the value of pearson product moment (r) is 0.862. The value of the Pearson product moment means that there is a very close relationship between the product packaging boxes with gross revenue and P-value is 0.05 so it was concluded that the relationship is significant. Keywords: product packaging, sales strategy, online system, pearson product moment, P-value.